Evolution of Aminoacyl-tRNA Synthetases—Analysis of Unique Domain Architectures and Phylogenetic Trees Reveals a Complex History of Horizontal Gene Transfer Events - Wolf, Yuri I.; Aravind, L.; Grishin, Nick V.; Koonin, Eugene V.

(untitled) (Genome Research, 1999)
Phylogenetic analysis of aminoacyl-tRNA synthetases (aaRSs) of all 20 specificities from completely sequenced bacterial, archaeal, and eukaryotic genomes reveals a complex evolutionary picture. Detailed examination of the domain architecture of aaRSs using sequence profile searches delineated a network of partially conserved domains that is even more elaborate than previously suspected. Several unexpected evolutionary connections were identified, including the apparent origin of the β-subunit of bacterial GlyRS from the HD superfamily of hydrolases, a domain shared by bacterial AspRS and the B subunit of archaeal glutamyl-tRNA amidotransferases, and another previously undetected domain that is conserved in a subset of ThrRS, guanosine polyphosphate hydrolases and synthetases, and a family of GTPases. Comparison of domain architectures and multiple alignments resulted in the delineation of synapomorphies—shared derived characters, such as extra domains or inserts—for most of the aaRSs specificities. These synapomorphies partition sets of aaRSs with the same specificity into two or more distinct and apparently monophyletic groups. In conjunction with cluster analysis and a modification of the midpoint-rooting procedure, this partitioning was used to infer the likely root position in phylogenetic trees. The topologies of the resulting rooted trees for most of the aaRSs specificities are compatible with the evolutionary “standard model” whereby the earliest radiation event separated bacteria from the common ancestor of archaea and eukaryotes as opposed to the two other possible evolutionary scenarios for the three major divisions of life. For almost all aaRSs specificities, however, this simple scheme is confounded by displacement of some of the bacterial aaRSs by their eukaryotic or, less frequently, archaeal counterparts. Displacement of ancestral eukaryotic aaRS genes by bacterial ones, presumably of mitochondrial origin, was observed for three aaRSs. In contrast, there was no convincing evidence of displacement of archaeal aaRSs by bacterial ones. Displacement of aaRS genes by eukaryotic counterparts is most common among parasitic and symbiotic bacteria, particularly the spirochaetes, in which 10 of the 19 aaRSs seem to have been displaced by the respective eukaryotic genes and two by the archaeal counterpart. Unlike the primary radiation events between the three main divisions of life, that were readily traceable through the phylogenetic analysis of aaRSs, no consistent large-scale bacterial phylogeny could be established. In part, this may be due to additional gene displacement events among bacterial lineages. Argument is presented that, although lineage-specific gene loss might have contributed to the evolution of some of the aaRSs, this is not a viable alternative to horizontal gene transfer as the principal evolutionary phenomenon in this gene class.[Complete multiple alignments of all aaRSs from complete genomes as well as the alignments of conserved regions used for phylogenetic tree construction are available at ftp://ncbi.nlm.nih.gov/pub/koonin/aaRS]